Systematic strengthening scenarios for determination of most suitable retrofitting approach in a low-rise RC building - Sena Sayar; Baris Sayin (Case Studies in Construction Materials, 2021)
The aim of this study was to determine most suitable strengthening approach in a reinforced concrete (RC) building using numerical analyses. The entire process is illustrated using a case study for a five-story RC framed building. To determine the seismic performance level, numerical simulations were performed through pushover analysis. Then, a retrofitting approach is presented for the building that does not meet current regulations. Five different strengthening proposals were presented for the building to meet the current requirements. After the examination of the proposals, only one strengthening proposal was deemed the most suitable solution. This proposal includes addition of new shear walls to the building. In this proposal, lateral drifts are reduced and the torsional moment deformation effect is minimized. Also, inter-story drifts decreased and the shear force and moment capacities increased. This paper can be utilized by researchers and practitioners in retrofitting approaches for low-rise RC buildings which represent a significant proportion of the building stock.